Removal of acetic acid from aqueous post-fermentation streams and fermented beverages using membrane contactors - Kaya, Ezgi; Hasanoglu, Ayca (WILEY, 2022)
BACKGROUND: The removal of volatile organic acids from aqueous post-fermentation wastewater streams and spoiled fermented liquid food was investigated using hollow-fiber membrane contactors. Acetic acid, being the most common volatile acid in post-fermentation products, was used to prepare acidic feed solutions. 1200-4000 ppm of aqueous acetic acid solutions with and without ethanol were prepared to assess the acid removal. Aqueous acetic acid solutions were used as model wastewater, while ethanol was included in the feed solutions to simulate the fermented beverages. Furthermore, the experiments were carried out using real spoiled wine to remove the excess acid. The feed solution was circulated through the shell side of the membrane contactor, while a reactive stripping solution of NaOH was circulated on the lumen side. Thus the acetic acid was transferred to the stripping solution by chemical absorption. RESULTS: The effect of several process parameters including feed and stripping solution concentrations, temperature and solution flow rates on acid removal rate was investigated. Temperature had the most important effect on mass transfer. Experiments showed that acetic acid can be removed from aqueous solutions and recovered in the stripping phase efficiently. Up to 86% of the acetic acid could be removed from the feed solution. CONCLUSION: This process is found to be effective for volatile organic acid removal from both industrial aqueous post-fermentation waste streams and spoiled fermented liquid food. The theoretical model developed for the acetic acid transfer allows a flexible and predictable design of the system for further scale-up studies. (c) 2022 Society of Chemical Industry (SCI).
Keywords: volatile acid removal; acetic acid; membrane contactor; fermentation product; VOLATILE FATTY-ACIDS; HOLLOW-FIBER MEMBRANE; AMMONIA REMOVAL; RECOVERY; WATER; EXTRACTION; SEPARATION; WINE; DEALCOHOLIZATION; Biotechnology & Applied Microbiology; Chemistry; Engineering